A study of wet deposition flux using a sequential sampling technique - (:unkn) unknown (My University, 2011)
The influence of washout scavenging on the removal processes of SO4 2-, NO3 - and Cl- ions were investigated using sequential rain sampling. For this purpose this study investigates the variation of these ions in precipitation using the sequential rain sampling and relationships of the wet deposition flux to the rain intensity and ion concentration were introduced. We carried out sequential rain sampling for five different rain events sampled in Istanbul on a) March 14th, 2008 b) March 20th, 2008 c) March 25th, 2008 d) April 6th, 2008 and e) May 4th, 2008. The correlation coefficient between SO4 2- and NO3 - which have main source domestic heating and industrial activities was calculated as 0.80, however inverse relation between NO3 - and Cl- which have different sources was found. The correlation between these ions was calculated as -0.60. Correlation coefficients between rain intensity and wet deposition flux for SO4 2-, NO3 - and Cl- calculated as 0.99, 0.94, 0.95 respectively. On the other hand weak relation was found between wet deposition flux and ion correlations. These results indicated that rain intensity has more dominant mechanism for wet deposition compression to the ion concentrations. © SGEM2011 All Rights Reserved by the International Multidisciplinary Scientific GeoConference SGEM.
Keywords: Below-cloud scavenging; Rain sampling; Washout process